2020
DOI: 10.17844/jphpi.v23i1.30887
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kandungan Logam Berat pada Kerang Lokan (Geloina erosa) di Perairan Aceh Barat

Abstract: Pesatnya pertumbuhan industri di wilayah pesisir Aceh Barat diduga menjadi sumber pencemaran logam berat di perairan dan terakumulasi pada biota laut, salah satunya yaitu kerang lokan (Geloina erosa). Penelitian ini bertujuan untuk menganalisis kandungan logam berat Hg, Cd, Pb, Cu, As, dan Zn pada kerang lokan mentah dan rebus, serta menentukan batas toleransi konsumsi kerang lokan yang mengandung logam berat. Pengambilan sampel kerang lokan dilakukan di 3 stasiun, yaitu perairan Peunaga Rayeuk, Ujong Baroh, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In Aceh itself, the heavy metal analysis in water, sediments, and fish from aquatic environment have been reported (Ukhty et al, 2020;Rizkiana et al, 2017;Supriatno & Lelifajri, 2009). Nonetheless, another study conducted in Riau Islands Province, Indonesia, reported significant contamination of Pb in Nerita lineata, with the minor presence of other heavy metals (Cu and Zn) (Sari et al, 2016).…”
Section: Distribution Pattern Of Pb and Zn Contamination In Rivers Ne...mentioning
confidence: 99%
“…In Aceh itself, the heavy metal analysis in water, sediments, and fish from aquatic environment have been reported (Ukhty et al, 2020;Rizkiana et al, 2017;Supriatno & Lelifajri, 2009). Nonetheless, another study conducted in Riau Islands Province, Indonesia, reported significant contamination of Pb in Nerita lineata, with the minor presence of other heavy metals (Cu and Zn) (Sari et al, 2016).…”
Section: Distribution Pattern Of Pb and Zn Contamination In Rivers Ne...mentioning
confidence: 99%